THE EFFECTIVENESS OF USING SUBTITLED ANIMATED CARTOON IN IMPROVING STUDENT’S VOCABULARY MASTERY AT GRADE VIII OF SMP N 3 PADANGSIDIMPUAN - Shoufi Nisma Dewi; Marwah Marwah; Khairunnisah Khairunnisah; Novria Grahmayanuri (Linguistik : Jurnal Bahasa dan Sastra, 2025)
The aim of this research was to find out the The Effectiveness of Using Subtitle Animated Cartoon in Improving Students’ Vocabulary Mastery at Grade VIII of SMP N 3 Padangsidimpuan. This research conducted by using Quantitative method with a pre-experimental design with one group of pre-test and post-test. This research population consisted of eighth grade students at SMP N 3 Padangsidimpuan, with the research sample being Class VIII-3, which consisted of 32 Students, selected by purposive sampling technique. The Data from this research, collected from the results of pre-test and post-test materials and used as an assessment to determine how the assessment of students ' knowledge before and after using Subtitled animated cartoon as a medium of teaching and learning. The result of this research revealed that using English cartoon films as a media of teaching and learning is effective for students in eighth grade students of SMP N 3 Padangsidimpuan in improving their vocabulary mastery especially word meaning and word classes such as noun and verb. This is demonstrated by how much the student's grades have improved. where the pre-test mean score of students is 30.34 and the post-test mean score of students is 71.06, indicating a 134.21% increase in students in this research. Furthermore, data analysis results show that the value of t-test (15.55) is greater than the value of t-table (2.040). Based on these findings, it is possible to conclude that there is a significant difference in students' "vocabulary mastery before and after they use English cartoon film as a media of teaching and learning process," demonstrating that English cartoon film is effective for improving students' vocabulary mastery.